Review of NASA's Planned Mars Program (The National Academies Press, 1996)
Keywords: Space and Aeronautics

Review of the Research Program of the Partnership for a New Generation of Vehicles: Second Report - Transportation Research Board (The National Academies Press, 1996)
Keywords: Engineering and Technology

National Science Education Standards - National Research Council (The National Academies Press, 1996)
Americans agree that our students urgently need better science education. But what should they be expected to know and be able to do? Can the same expectations be applied across our diverse society? These and other fundamental issues are addressed in National Science Education Standards—a landmark development effort that reflects the contributions of thousands of teachers, scientists, science educators, and other experts across the country. The National Science Education Standards offer a coherent vision of what it means to be scientifically literate, describing what all students regardless of background or circumstance should understand and be able to do at different grade levels in various science categories. The standards address:
Keywords: Education

Biodiversity Conservation in Transboundary Protected Areas - National Research Council (The National Academies Press, 1996)
Recognizing the increasing rate of species loss on a global scale and that neither pollution nor ecosystems respects political boundaries, cooperation on many different levels is required to conserve biodiversity. This volume uses four protected areas that Poland shares with its neighbors as case studies to explore opportunities to integrate science and management in transboundary protected areas in Central Europe for the conservation of biodiversity. Specific topics include biodiversity conservation theories and strategies, problems of wildlife management, and impacts of tourism and recreational use on protected areas.
Keywords: Environment and Environmental Studies; Biology and Life Sciences

From Analysis to Action: Undergraduate Education in Science, Mathematics, Engineering, and Technology (The National Academies Press, 1996)
Keywords: Education

New Materials for Next-Generation Commercial Transports - National Research Council (The National Academies Press, 1996)
The major objective of this book was to identify issues related to the introduction of new materials and the effects that advanced materials will have on the durability and technical risk of future civil aircraft throughout their service life. The committee investigated the new materials and structural concepts that are likely to be incorporated into next generation commercial aircraft and the factors influencing application decisions. Based on these predictions, the committee attempted to identify the design, characterization, monitoring, and maintenance issues that are critical for the introduction of advanced materials and structural concepts into future aircraft.
Keywords: Engineering and Technology; Space and Aeronautics

Review of Systemization of the Tooele Chemical Agent Disposal Facility - National Research Council (The National Academies Press, 1996)
In 1993, at Tooele Army Depot, Utah, the Army completed construction of the Tooele Chemical Agent Disposal Facility (TOCDF), the first complete facility for destruction of lethal unitary chemical agents and munitions to be built in the continental United States. The TOCDF will employ the Army's baseline incineration system to destroy the depot's increment of the nation's aging unitary chemical stockpile. This book assesses Army changes and improvements to the TOCDF in response to recommendations contained in earlier reports of the committee. It assesses aspects of the facility's readiness for safe agent handling and destruction operations, its agent monitoring system, and its site specific risk assessment.
Keywords: Environment and Environmental Studies

Review and Evaluation of Alternative Chemical Disposal Technologies - National Research Council (The National Academies Press, 1996)
In 1994 the National Research Council published Recommendations for the Disposal of Chemical Agents and Munitions, which assessed the status of various alternative destruction technologies in comparison to the Army's baseline incineration system. The volume's main finding was that no alternative technology was preferable to incineration but that work should continue on the neutralization technologies under Army consideration. In light of the fact that alternative technologies have evolved since the 1994 study, this new volume evaluates five Army-chosen alternatives to the baseline incineration system for the disposal of the bulk nerve and mustard agent stored in ton containers at Army sites located in Newport, Indiana, and Aberdeen, Maryland, respectively. The committee assessed each technology by conducting site visits to the locations of the technology proponent companies and by meeting with state regulators and citizens of the affected areas. This volume makes recommendations to the Army on which, if any, of the five technologies has reached a level of maturity appropriate for consideration for pilot-scale testing at the two affected sites.
Keywords: Environment and Environmental Studies

Accelerated Aging of Materials and Structures: The Effects of Long-Term Elevated-Temperature Exposure (The National Academies Press, 1996)
Keywords: Engineering and Technology

Expanding the Uses of Naval Ocean Science and Technology (The National Academies Press, 1996)
Keywords: Engineering and Technology

Evaluation of the U.S. Department of Defense Persian Gulf Comprehensive Clinical Evaluation Program - Institute of Medicine (The National Academies Press, 1996)
Keywords: Health and Medicine

Engineering Research and Technology Development on the Space Station (The National Academies Press, 1996)
Keywords: Space and Aeronautics

Assessing Knowledge of Retirement Behavior - National Research Council (The National Academies Press, 1996)
This book brings together in one volume what researchers have learned about workers, employers, and retirees that is important for formulating retirement income policies. As the U.S. population ages, there is increasing uncertainty about the solvency of the Social Security and Medicare systems and the adequacy of private pensions to provide for people's retirement needs. The volume covers such critical behaviors as workers' decisions to retire, people's choices of saving over consumption, and employers' decisions about hiring older workers and providing pension and health care benefits. Also covered are trends in mortality, health status, and health care costs that are key to projecting the likely costs and effects of alternative retirement income security policies and a strategy for combining data and research knowledge into a policy modeling framework.
Keywords: Behavioral and Social Sciences

River Resource Management in the Grand Canyon - National Research Council (The National Academies Press, 1996)
Federal management of water is undergoing a change that involves a drastic reduction in the number of new water projects and an increase in emphasis on the quality of water management. This book summarizes and analyzes environmental research conducted in the lower Colorado River below the Glen Canyon Dam under the leadership of the Bureau of Reclamation. It reviews alternative dam operations to mitigate impacts in the lower Colorado riverine environment and the strengths and weaknesses of large federal agencies dealing with broad environmental issues and hydropower production. While many problems remain to be solved, the Bureau of Reclamation through the Glen Canyon area. The lessons of GCES are transferable to other locations and could be the basis for a new era in the management of western waters.
Keywords: Earth Sciences; Environment and Environmental Studies

(NAS Colloquium) Genetic Engineering of Viruses and Viral Vectors (The National Academies Press, 1996)
Keywords: Biology and Life Sciences; Environment and Environmental Studies

Affordable Cleanup?: Opportunities for Cost Reduction in the Decontamination and Decommissioning of the Nation's Uranium Enrichment Facilities - National Research Council (The National Academies Press, 1996)
The Energy Policy Act of 1992 called on the National Academy of Sciences to conduct a study and provide recommendations for reducing the costs of decontaminating and decommissioning (D&D) the nation's uranium enrichment facilities located at Oak Ridge, Tennessee; Raducah, Kentucky; and Portsmouth, Ohio. This volume examines the existing plans and cost estimates for the D&D of these facilities, including such elements as technologies, planning and management, and identifies approaches that could reduce D&D costs. It also assesses options for disposition of the large quantities of depleted uranium hexafluoride that are stored at these sites.
Keywords: Environment and Environmental Studies; Engineering and Technology

Risk & Innovation: Small Companies in Six Industries: Background Papers Prepared for the NAE Risk and Innovation Study (The National Academies Press, 1996)

Using Performance Monitoring to Improve Community Health: Conceptual Framework and Community Experience - Institute of Medicine (The National Academies Press, 1996)
Keywords: Health and Medicine

Preventing and Mitigating AIDS in Sub-Saharan Africa: Research and Data Priorities for the Social and Behavioral Sciences - National Research Council (The National Academies Press, 1996)
The AIDS epidemic in Sub-Saharan Africa continues to affect all facets of life throughout the subcontinent. Deaths related to AIDS have driven down the life expectancy rate of residents in Zambia, Kenya, and Uganda with far-reaching implications. This book details the current state of the AIDS epidemic in Africa and what is known about the behaviors that contribute to the transmission of the HIV infection. It lays out what research is needed and what is necessary to design more effective prevention programs.
Keywords: Health and Medicine

Shipbuilding Technology and Education (The National Academies Press, 1996)
The U.S. shipbuilding industry now confronts grave challenges in providing essential support of national objectives. With recent emphasis on renewal of the U.S. naval fleet, followed by the defense builddown, U.S. shipbuilders have fallen far behind in commercial ship construction, and face powerful new competition from abroad. This book examines ways to reestablish the U.S. industry, to provide a technology base and R&D infrastructure sustaining both commercial and military goals. Comparing U.S. and foreign shipbuilders in four technological areas, the authors find that U.S. builders lag most severely in business process technologies, and in technologies of new products and materials. New advances in system technologies, such as simulation, are also needed, as are continuing developments in shipyard production technologies. The report identifies roles that various government agencies, academia, and, especially, industry itself must play for the U.S. shipbuilding industry to attempt a turnaround.
Keywords: Engineering and Technology